Perlindungan Hukum Terhadap Kekerasan dalam Perkawinan: Tinjauan Hukum Islam dan RKUHP - Qadriah, Fauza; Panjaitan, Budi Sastra (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2024)
This article aims to understand that marital violence as a form of sexual violence against women that occurs in a marital relationship. One of the causes of violence in marriage is the patriarchal culture that is still inherent in people's lives. This patriarchal culture allegedly causes gender injustice which results in the emergence of discrimination against women. This research is normative legal research because it uses a legislative approach with a focus on legal principles and legal principles as well as conceptual methods. The point of view of this writing is expressed by compiling verses of the Qur'an and hadith using maqasid as-shari'ah. The findings of this study show that efforts to handle a wife who is a victim of marital violence must be in line with the purpose of Islamic law, namely the protection of the five main principles in Islam, namely preserving religion, soul, intellect, descendants and property. Marimal violence is prohibited in marriage, as it has a long-term negative impact on the wife. In addition, violence in marriage that is prohibited by law can result in mafāsid muharramāt al-tahṣîl (the bad effects of something that is haram) or mafāsid makrūhāt al-tahṣîl (the bad effects of something makruh). Keywords: Violence in marriage, Domestic Violence, Patriarchy, Maqasid As-shari'ah, Islamic Law